1995
DOI: 10.1002/j.1556-6978.1995.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Early Childhood Family Influence and Counselor Effectiveness: An Exploratory Study

Abstract: This study found a significant correlation between counselor effectiveness and negative perceptions of early childhood family influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
4
9
0
Order By: Relevance
“…Whereas this result is inconsistent with theorizing, it is consistent with some previous research (e.g., Bartholomew & Horowitz, 1991;Searle & Meara, 1999), suggesting that preoccupation with relationships is related to higher levels of sociability and interpersonal warmth and to an intense focus on the emotions of others. Also, our results are consistent with more tangential research on counselor trainees (Watts et al, 1995;Wilcoxon et al, 1989) suggesting that negative perceptions of the family of origin are related to higher levels of counseling skill. Wolgien and Coady (1997), through interviews of effective counselors, found that the majority of those interviewed attributed some portion of their counseling effectiveness to their ability to deal with distress in their family of origin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Whereas this result is inconsistent with theorizing, it is consistent with some previous research (e.g., Bartholomew & Horowitz, 1991;Searle & Meara, 1999), suggesting that preoccupation with relationships is related to higher levels of sociability and interpersonal warmth and to an intense focus on the emotions of others. Also, our results are consistent with more tangential research on counselor trainees (Watts et al, 1995;Wilcoxon et al, 1989) suggesting that negative perceptions of the family of origin are related to higher levels of counseling skill. Wolgien and Coady (1997), through interviews of effective counselors, found that the majority of those interviewed attributed some portion of their counseling effectiveness to their ability to deal with distress in their family of origin.…”
Section: Discussionsupporting
confidence: 90%
“…Their results suggested that the lower the perceived autonomy and intimacy in the early childhood family experiences of novice counselors, the higher their interpersonal-facilitation skill level. The findings of Watts, Trusty, Canada, and Harvill (1995) are similar. Watts et al investigated the relationship between perceived early family influence and counselor effectiveness in master's-level practicum students.…”
Section: Adult Attachment and Empathysupporting
confidence: 66%
See 1 more Smart Citation
“…Counseling students with more effective family-oforigin relationships correlates with increased counselor effectiveness (e.g., Trusty, Showron, Watts, & Parrillo, 2004;Watts, Trusty, Canada, & Harvill, 1995;Wilcoxon, Walker, & Hovestadt, 1989;Wolgien & Coady, 1997). Trusty, Showron, Watts, and Parrillo (2004) concluded that ''perhaps counselor-trainees who are more real with themselves are more real with others and therefore more attractive (i.e., friendly, likable, sociable, and warm) in counseling'' (p. 11).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, contrary to the concern that early trauma may compel individuals to become mental health professionals as a defense (repetition compulsion, acting out, reaction formation or another), several studies have suggested that early trauma may confer an added strength to the clinical skills of the practitioner. For example, in more than one survey of master's level clinical practicum students, the perceived quality of their early relationships with their parents had an inverse correlation with their effectiveness as therapists (Watts et al, 1995;Wilcoxon et al, 1989). Furthermore, several studies have found association between the therapist level of integration and meaning making of early family hardship and the likelihood that they will be perceived by their supervisors and patients as more skillful and effective (Cushway, 1996;Miller & Baldwin, 2000;Wolgien & Coady, 1997).…”
mentioning
confidence: 89%